Lab coat 2 - Hasrin, Noradriana Izzaty; Wazir, Nursuhada; Othman, Siti Amira (Penerbit UTHM, 2020)
In past previous years, tremendous of safety product created, invented and merchandized worldwide. These products are made with purposes in which to minimizing the risks while dealing with chemical and hazardous equipment in any working space especially laboratory. In order to ensure safety of lab worker is on the optimal level, manufacturers and importers are responsible to fulfill the safety specification. This requirement should involves providing instruction to safety operate the product, placing an appropriate label on the product, also concerning about the material used in developing product.